2015
DOI: 10.3920/bm2014.0067
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotics and probiotics in irritable bowel syndrome and inflammatory bowel disease in children

Abstract: Underlying pathophysiological mechanisms of irritable bowel syndrome (IBS), a common disorder characterized by abdominal pain associated to a change in stool consistency or frequency, include low-grade inflammation and intestinal microbiota changes. Few and disappointing data are available for prebiotics. A few controlled trials (RCTs) of probiotics are instead available with favourable effects, although most are limited by suboptimal design and small sample size. A recent report from the Rome foundation group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…and Bifidobacterium spp. are generally regarded as beneficial, especially in the context of mucosal immunity and administration of probiotic supplements containing these bacteria have been found to be highly beneficial in the context of GI disease and inflammation [77-80]. These bacteria are also known to provide B and K vitamins to the host which are necessary for a variety of metabolic processes [71].…”
Section: Microbial Dysbiosis In Hiv Infectionmentioning
confidence: 99%
“…and Bifidobacterium spp. are generally regarded as beneficial, especially in the context of mucosal immunity and administration of probiotic supplements containing these bacteria have been found to be highly beneficial in the context of GI disease and inflammation [77-80]. These bacteria are also known to provide B and K vitamins to the host which are necessary for a variety of metabolic processes [71].…”
Section: Microbial Dysbiosis In Hiv Infectionmentioning
confidence: 99%
“…The most currently used drugs encompass rifaximin, probiotics, prebiotics, fibers, antispasmodics, laxatives and dietary interventions [148-155]. …”
Section: Treatmentmentioning
confidence: 99%
“…Diarrhea, constipation and intestinal inflammation are the main symptoms of the patients with IBD and IBS [1112]. Clinical and epidemiological studies indicate that the inflammation is found from the jejunum to the rectum in both IBS and IBD [1314151617].…”
Section: Introductionmentioning
confidence: 99%